General psychopathology, internalising and externalising in children and functional outcomes in late adolescence. (2nd May 2019) - Sallis, Hannah; Szekely, Eszter; Neumann, Alexander; Jolicoeur‐Martineau, Alexia; van IJzendoorn, Marinus; Hillegers, Manon; Greenwood, Celia M.T.; Meaney, Michael J; Steiner, Meir; Tiemeier, Henning; Wazana, Ashley; Pearson, Rebecca M.; et al.
Abstract : Background: Internalising and externalising problems commonly co‐occur in childhood. Yet, few developmental models describing the structure of child psychopathology appropriately account for this comorbidity. We evaluate a model of childhood psychopathology that separates the unique and shared contribution of individual psychological symptoms into specific internalising, externalising and general psychopathology factors and assess how these general and specific factors predict long‐term outcomes concerning criminal behaviour, academic achievement and affective symptoms in three independent cohorts. Methods: Data were drawn from independent birth cohorts (Avon Longitudinal Study of Parents and Children (ALSPAC), N = 11, 612; Generation R, N = 7, 946; Maternal Adversity, Vulnerability and Neurodevelopment (MAVAN), N = 408). Child psychopathology was assessed between 4 and 8 years using a range of diagnostic and questionnaire‐based measures, and multiple informants. First, structural equation models were used to assess the fit of hypothesised models of shared and unique components of psychopathology in all cohorts. Once the model was chosen, linear/logistic regressions were used to investigate whether these factors were associated with important outcomes such as criminal behaviour, academic achievement and well‐being from late adolescence/early adulthood. Results: The model that included specific factors for internalising/externalising and a general psychopathology factor capturing variance shared between symptoms regardless of their classification fits well for all of the cohorts. As hypothesised, general psychopathology factor scores were predictive of all outcomes of later functioning, while specific internalising factor scores predicted later internalising outcomes. Specific externalising factor scores, capturing variance not shared by any other psychological symptoms, were not predictive of later outcomes. Conclusions: Early symptoms of psychopathology carry information that is syndrome‐specific as well as indicative of general vulnerability and the informant reporting on the child. The 'general psychopathology factor' might be more relevant for long‐term outcomes than specific symptoms. These findings emphasise the importance of considering the co‐occurrence of common internalising and externalising problems in childhood when considering long‐term impact.